The Improvement Of Students’ Vocabulary Achievement By Using Direct Method Of SMP Wiyatama Bandar Lampung - Futri Nurhayani (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The objective of this research was aimed to find out the improvement of students’ vocabulary achievement by using direct method of SMP Wiyatama Bandar Lampung. Bandar Lampung: English Education Study Program, Faculty of Teacher Training and Education, Bandar Lampung University. The main objective of this research was aimed to identify whether the use Direct Method was effective in improving the students’ vocabulary achievement.In learning a language, the first step students will be watch a video. In order to learn a language well, she or he must be watching the video. Data were collected by incorporating two pre-test and two post-test in experimental group and control group. Treatment using the application of direct method that administered in experimental group, while control group received traditional teaching (TT). Data analysis was attempted using t-Test for two group design. Result indicated that p-value 1% = 2,66, 5% = 2,00, and t-value = 7,6. It means p-value is smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The researcher concluded that The Improvement of Students’ Vocabulary by using Direct Method more than traditional teaching. So, the students who taught by using Direct Method will perform better and get the higher score than the students who only taught y traditional teaching.